Pencils of Euler Triples, I - Čerin, Zvonko (Sarajevo Journal of Mathematics, 2024)
In this paper we will study the families of triples (u,v,w) of elements in a commutative ring r with the property that v w+n=u^2, w u+n=v^2 and u v+n=w^2 for some n, ... 2000 Mathematics Subject Classification. Primary 11B37, 11B39, 11D09